A phosphorylation switch in the Mediator MED15 controls cellular senescence and cognitive decline - Haozheng Li; Yuanming Zheng; Chunlei Yuan; Jiayi Wang; Xiaying Zhao; Ming Yang; Defei Xiong; Yenan Yang; Yunpeng Dai; Yiming Gao; Yuqi Wang; Lei Xue; et al. (Cell Discovery)
Abstract A hallmark of aging is chronic systemic inflammation, which is exacerbated by the hypersecretory aging phenotype known as the senescence-associated secretory phenotype (SASP). How the SASP is initiated to accelerate tissue inflammation and aging is an outstanding question in aging biology. Here, we showed that phosphorylation of the Mediator subunit MED15 at T603 is able to control the SASP and aging. Transforming growth factor-β selectively induces CDK1-mediated MED15 T603 phosphorylation to control SASP gene expression. The MED15 T603 dephosphorylated mutant (T603A) inhibits the SASP and cell senescence, whereas the T603 phosphorylation-mimicking mutant (T603D) has the opposite effect. Mechanistically, forkhead box protein A1 preferentially binds to unphosphorylated but not phosphorylated MED15 at T603 to suppress SASP gene expression. Notably, aging mice harboring dephosphorylated mutation in this phosphosite exhibit improved learning and memory through the attenuation of the SASP across tissues. Overall, our study indicates that MED15 T603 phosphorylation serves as a control switch for SASP production, which underlies tissue aging and cognitive decline and provides a novel target for age-related pathogenesis.